Dynamiczna analiza rozwoju społeczeństwa informacyjnego - Anna Janiga-Ćmiel (Ekonomiczne Problemy Usług, 2016)
The paper examines the development of Polish information society as well as the information society of selected countries in the period from 2005 to 2015 (Luxembourg, Poland, Bulgaria, Germany, Greece). The theory of the construction of a full-factor multivariate GARCH model and its estimation method are discussed. The aim of the studies discussed in the paper is an analysis of the interrelations between the information society of Poland and selected EU countries. The multivariate GARCH models showing mutual relative interrelations within the dynamics of empirical distributions, particularly within the dynamics of the expected values and variances, will be presented.